Moral Learning with a Deep Learning Approach at Elementary School - Rohana Desy Kurniawati; Djamaluddin Perawironegoro; Arif Rahman; Yusron Masduki; Sutarman Sutarman (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Moral learning in elementary schools plays an important role in shaping students' character, especially respectful behavior towards teachers. However, at SD Negeri Blubuk, student behavior is still found that shows low respect, as well as moral learning that tends to be textual and less connected to students' real experiences. This study aims to analyze the implementation of moral learning with a deep learning approach at SD Negeri Blubuk. This study uses a qualitative approach with a case study type carried out at SD Negeri Blubuk, Kulon Progo. Data were collected through observation, interviews, and documentation with purposively selected principals, teachers, students, and parents. The data was analyzed using an interactive analysis model with triangulation (sources and techniques) to ensure the validity of the findings.  The results of the study concluded that moral learning with a deep learning approach at SD N Blubuk was carried out systematically through the stages of planning, implementation, and continuous evaluation which were strengthened by school culture and habituation programs. This approach encourages students to understand moral values in depth, apply them in daily life, and reflect on them through meaningful learning experiences. The implementation integrates the principles of mindful, meaningful, and joyful learning deep learning which are packaged in a learning framework including pedagogical practices, the creation of a conducive learning environment, partnerships, and the optimal use of digital technology.